2018
DOI: 10.3390/f9040175
|View full text |Cite
|
Sign up to set email alerts
|

Day Extension with Far-Red Light Enhances Growth of Subalpine Fir (Abies lasiocarpa (Hooker) Nuttall) Seedlings

Abstract: Subalpine fir (Abies lasiocarpa (Hooker) Nuttall), which is native to western North America, is of considerable interest for Christmas tree production in northern Europe. Seedlings are usually grown from seeds under combined nursery greenhouse/outdoors conditions, but commonly show early growth cessation in the nursery, resulting in small plants for field transplanting. This increases the production time and makes the seedlings vulnerable to stressors at the planting site. Day extension with far-red (FR) light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…Several studies have suggested differential sensitivities of plant growth to light quantity and quality depending on their latitudinal origin [14][15][16][20][21][22][23] showing an interaction between the effect of light qualities and latitude [14,15]. The analysis of such data in the current study (see Figure 4A,B; Figure S1), also showed a distinct growth response to changed R:FR ratios depending on the latitudinal origin of the plants studied.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Several studies have suggested differential sensitivities of plant growth to light quantity and quality depending on their latitudinal origin [14][15][16][20][21][22][23] showing an interaction between the effect of light qualities and latitude [14,15]. The analysis of such data in the current study (see Figure 4A,B; Figure S1), also showed a distinct growth response to changed R:FR ratios depending on the latitudinal origin of the plants studied.…”
Section: Discussionsupporting
confidence: 70%
“…A very strong effect of the weather conditions at low solar elevation angles was found for the R:FR ratio, possibly partly explaining the larger differences between natural R:FR ratio measurements reported by previous authors (e.g., [1,28,29]). Although changes of the R:FR ratio in the presented magnitudes ( Figure 2) have shown biological effects in short-term experiments with herbaceous plants [30], this effect has not been found in the few tree species investigated so far [15,16]. In contrast, many annual plants show high plasticity to lower fluctuation on the R:FR ratio conditions [31].…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations